A history of dentistry in Canada - Gullett, D. W. (Heritage, 1971)
"Beginning with the earliest records available describing the dental health of the Indians before the arrival of European settlers, Dr Gullett gives a detailed and carefully documented history of dentistry in Canada. He describes the unscrupulous tramp dentists who roamed the countryside years ago as well as their respectable contemporaries, and he traces the development of practice, education, and professional associations, as dentistry developed from an art to a science. The author spent five years gathering information for this book from public archives, libraries, personal interviews, and the records of the profession. The result is a lively and readable story told with a continuing concern for health services."--Publisher's description